A Better Start: Protocol for a National Evaluation of an Area-based Intervention Programme on Early Life Outcomes - Barlow, J; Beake, S; Bick, D; Bryson, C; Day, L; Gilby, N; Glover, V; Knibbs, S; Leyland, A; Lindsay, G; Mathers, S; McKenna, K; et al. (BMJ Publishing Group, 2017)
Introduction Pregnancy and the first few years of a child’s life are important windows of opportunity in which to equalize life chances. A Better Start (ABS) is an area-based intervention being delivered in five areas of socioeconomic disadvantage across England. This protocol describes an evaluation of the impact and cost-effectiveness of ABS. Methods and analysis The evaluation of ABS comprises a mixed-methods design including impact, cost effectiveness and process components. It involves a cohort study in the five ABS areas and 15 matched comparison sites (n=2885), beginning in pregnancy in 2017 and ending in 2024 when the child is age 7, with a separate cross-sectional baseline survey in 2016/17. Process data will include a profiling of the structure and services being provided in the five ABS sites at baseline and yearly thereafter, and data regarding the participating families and the services that they receive. Eligible participants will include pregnant women living within the designated sites, with recruitment beginning at 16 weeks of pregnancy. Data collection will involve interviewer-administered and self-completion surveys at eight time-points. Primary outcomes include nutrition, socio-emotional development, speech, language and learning. Data analysis will include the use of propensity score techniques to construct matched programme and comparison groups, and a range of statistical techniques to calculate the difference in differences between the intervention and comparison groups. The economic evaluation will involve a within-cohort study economic evaluation to compare individual-level costs and outcomes, and a decision analytic cost-effectiveness model to estimate the expected incremental cost per unit change in primary outcomes for ABS in comparison to usual care. Ethics and dissemination Ethical approval to conduct the study has been obtained. The learning and dissemination workstream involves working within and across the sites to generate learning via communities of practice and a range of learning and dissemination events. STRENGTHS AND LIMITATIONS OF STUDY • The study involves a large longitudinal design with matched comparison sites • The designation of ABS areas was not random, and statistical matching will be used to select comparison areas and propensity score techniques will be used to match individual in ABS areas to individuals in comparison areas • Concurrent implementation data will provide important information about systems level change • Recruitment in pregnancy of disadvantaged women will present many difficulties and uptake may be low • Loss to follow-up by 7 years may be high